Molecular Characterization, Expression Pattern and Function Analysis of Glycine-Rich Protein Genes Under Stresses in Chinese Cabbage (Brassica rapa L. ssp. pekinensis) - Lu, Xiaonan; Cheng, Yaxiong; Gao, Ming; Li, Meilan; Xu, Xiaoyong (Frontiers in Genetics, 2020)
Plant Glycine-rich proteins (GRP), a superfamily with a glycine-rich domain, play an important role in various stresses such as high or low temperature stress and drought stress. GRP genes have been studied in many plants, but seldom in Chinese cabbage (Brassica rapa L. ssp. pekinensis). In this study, a total of 64 GRP genes were identified in Chinese cabbage by homology comparative analysis. The physical and chemical characteristics predicted by ProtParam tool revealed that 62.5% of BrGRPs were alkaline, 53.1% were stable, and 79.7% were hydrophilic. Conserved domain analysis by MEME and TBtools showed that 64 BrGRPs contained 20 of the same conserved motifs, based on which BrGRPs were classified into five main subclasses to clarify their evolutionary relationship. Our results demonstrated that The BrGRP genes were located on ten chromosomes and in three different subgenomes of Chinese cabbage, and 43 pairs of orthologous GRP genes were found between Chinese cabbage and Arabidopsis. According to the transcriptome data, 64 BrGRP genes showed abnormal expression under high temperature stress, 52 under low temperature stress, 39 under drought stress, and 23 responses to soft rot. A large number of stress-related cis-acting elements, such as DRE, MYC, MYB, and ABRE were found in their promoter regions by PlantCare, which corresponded with differential expressions. Two BrGRP genes-w546 (Bra030284) and w1409 (Bra014000), both belonging to the subfamily Subclass IVa RBP-GRP (RNA binding protein-glycine rich protein), were up-regulated under 150 mmol·L-1 NaCl stress in Chinese cabbage. However, the overexpressed w546 gene could significantly inhibit seed germination, while w1409 significantly accelerated seed germination under 100 mmol·L-1 NaCl or 300 mmol·L-1 mannitol stresses. In short, most BrGRP genes showed abnormal expression under adversity stress, and some were involved in multiple stress responses, suggesting a potential capacity to resist multiple biotic and abiotic stresses, which is worthy of further study. Our study provides a systematic investigation of the molecular characteristics and expression patterns of BrGRP genes and promotes for further work on improving stress resistance of Chinese cabbage.